PELATIHAN PENGGUNAAN SOFTWARE AUDACITY SEBAGAI MEDIA PENGEMAS MATERI AJAR YANG MENARIK - Silviana, Mery; Mirdayanti, Rina; Lindawati, Lindawati; Apriani, Wiwin; Yunina, Fitri (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2022)
Face-to-face restrictions on elementary school students during the pandemic force teachers to have creative and innovative ideas in conducting distance learning. Unlike learning for junior or senior high school students who have better understanding of lessons using simpler methods, elementary school students need more detailed methods of learning. Audacity is an application with script writing and voice recording techniques that are able to help elementary school students develop better understanding in distance lessons. Training on the application of interesting and innovative learning media using the Audacity application at SD Negeri 44 Banda Aceh aims to assist teachers at SD Negeri 44 Banda Aceh in using interesting and innovative software-based learning media with script writing and voice recording techniques, so that they can produce effective teaching materials that can be easily understood by students.